1984
DOI: 10.1001/archotol.1984.00800330025005
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Neck Disease: Evaluation by Computed Tomography

Abstract: \s=b\Computed tomographic (CT) scanning has been used in the preoperative examination of patients with head and neck cancer. Although early reports on the use of CT scanning for cervical lymphadenopathy were encouraging, the accuracy of CT in detecting nodal metastases has not been well established. Fifty consecutive patients underwent radical neck dissection and preoperative CT scanning. The clinical staging of the neck, CT diagnoses, and pathologic findings were correlated; CT accuracy was then compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 13 publications
1
37
0
1
Order By: Relevance
“…21 Close et al 22 found that the CT scan upstaged the clinically negative neck in 67% of cases of oral cavity and oropharyngeal carcinoma and several studies have shown a greater than 90% accuracy rate for CT scanning of pathologic neck disease. [17][18][19] In the current study, imaging had an 84% sensitivity rate in detecting pathologic lymph node disease in cN-positive patients. Since 1981, CT scanning has been used to evaluate cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 57%
“…21 Close et al 22 found that the CT scan upstaged the clinically negative neck in 67% of cases of oral cavity and oropharyngeal carcinoma and several studies have shown a greater than 90% accuracy rate for CT scanning of pathologic neck disease. [17][18][19] In the current study, imaging had an 84% sensitivity rate in detecting pathologic lymph node disease in cN-positive patients. Since 1981, CT scanning has been used to evaluate cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 57%
“…As a consequence, in these studies, a higher sensitivity results in a lower specificity and vice versa. For example, Stevens et al (12), Close et al (15), Hillsamer et al (9), and Friedman et al (11) found sensitivity rates of 97%, 86.5%, 84%, and 95% paired to a much lower specificity of 82%, 71%, 71%, and 77%, respectively. In contrast, Feinmesser et al (4) found a relatively low sensitivity of 60% with a higher specificity of 85%.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) imaging and computed tomography (CT) are useful (6-10); however, these are expensive and not always avail able. In addition, differentiation be tween nodes with and those without métastasés on the basis of radiologic characteristics only has a relatively low specificity (4,9,(11)(12)(13)(14)(15)(16)(17). Immuno logic assays may prove to be useful in the future but are still under investi gation (18), Ultrasound (US) of the neck combined with US-guided fineneedle aspiration biopsy (FNAB) was dem onstrated to be very accurate in the evaluation of regional metastatic disease (13,19,20).…”
Section: Methodsmentioning
confidence: 99%
“…CT seems to be better than MRI for the assessment of necrotic areas in lymph nodes. Close et al found that CT identified lymph node metastasis in 67% of cases of oral cavity and oropharyngeal carcinoma with clinically negative neck disease, and several studies have shown a greater than 80% accuracy rate for CT identification of pathologic neck disease [36,[56][57][58]. Extracapsular spread is characterized by irregular lymph node edges and the absence of fine fatty layers on CT/MRI [54], as well as the infiltration of adjacent structures.…”
Section: Clinical Evaluation For Metastatic Disease and Stagingmentioning
confidence: 99%